Understanding Social Accountability: Politics, Power and Building New Social Contracts - Hickey, Sam; King, Sophie (The Journal of Development Studies, 2016)
Calls to deepen levels of social accountability within social protecti on interventions need to be informed by the now extensive experience o f promoting social accountability in developing countries. Drawing on a systematic review of over 90 social accountability interventions, in cluding some involving social protection, this paper shows that politi cs and context are critical to shaping their success. We argue that th e politics of social protection and of social accountability resonate strongly with the broader project of transforming state-society relati ons in developing countries. This requires a reconceptualisation of so cial accountability and social protection in terms of the broader deve lopment of ‘social contracts’, and that the current emphasis on promot ing bottom-up forms of accountability needs to be balanced by efforts to strengthen and legitimise public authority in developing countries.